Endothelial Dysfunction and Angiogenesis in Autosomal Dominant Polycystic Kidney Disease - M. Fick-Brosnahan, Godela (Current Hypertension Reviews, 2013)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common potentially lethal hereditary disease. The hall mark of the disease is the development of innumerable cysts in kidneys and liver. However, a vascular phenotype including the early occurrence of hypertension, abnormalities in renal blood flow, intracranial and aortic aneurysms, spontaneous coronary and cervicocephalic artery dissections, and dolichoectasias of intracranial arteries is also part of the spectrum of ADPKD. While endothelial dysfunction occurs early in ADPKD and precedes the onset of hypertension, the pathogenesis of endothelial dysfunction has not been extensively studied. Development of endothelial dysfunction in ADPKD (as in other conditions characterized by endothelial dysfunction) has been linked to oxidative stress and vascular inflammation. Vascular dysfunction with increased contraction and decreased relaxation causes downstream tissue ischemia, a potent stimulus for angiogenesis. Evidence of angiogenesis on the surface of renal cysts has been documented in human ADPKD. In addition, high levels of angiogenic growth factors including vascular endothelial growth factor have been reported in cyst fluid and in the circulation of patients with ADPKD. In the following chapter we summarize recent studies examining the role and pathogenesis of endothelial dysfunction and neoangiogenesis in ADPKD.
Keywords: Autosomal dominant polycystic kidney disease